Proof in Mathematics Education, 1980-2020: An Overview - Gila Hanna; Christine Knipping (Korea Society of Educational Studies in Mathematics, 2020)
This paper looks at the evolution of ideas on the role of proof in mathematics education from 1980 to 2020, examining in particular the contributions of both theoretical and empirical research to the teaching of mathematical proof. In so doing, it describes some of the major epistemological themes that emerged in the last forty years, primarily in the philosophy of mathematics and in mathematical education, and informed both the mathematics curriculum and research in mathematics education. The paper also discusses selected research studies that shed light on the opportunities and limitations students face when they engage in proof. Finally, it describes briefly a number of developments in proof technology and the potential of automated theorem provers for enhancing the teaching of proof.